Two-wavelength digital holographic microscopy using speckle illuminations. (May 2020) - Funamizu, Hideki; Sugata, Kota; Uozumi, Jun; Aizu, Yoshihisa
Highlights: Two-wavelength DHM using speckle patterns is proposed and demonstrated. The DHM realizes spatial resolution enhancement and measurement range extension. The effect of the averaging process in the DHM on phase unwrapping is evaluated. 2-D SNR map against multiple holograms and spatial frequencies is presented. Abstract: Digital holographic microscopy (DHM) is actively investigated in the field of bio-imaging as a technique for quantitative phase microscopy. During recent years, the digital holographic technique for enhancing the spatial resolution using speckle patterns has been reported by several research groups. In this study, we have enhanced the spatial resolution and extended the measurement range of the shape measurement by applying a two-wavelength method to DHM using speckle illuminations.